2016
DOI: 10.18203/2349-2902.isj20164463
|View full text |Cite
|
Sign up to set email alerts
|

Negative laparotomy rates in acute abdomen: a declining trend

Abstract: INTRODUCTIONThe acute abdomen is one of the commonest causes of admission to the emergency surgical department. Acute abdomen is a condition of acute abdominal pain, vomiting and bowel complaints of less than 24 hour duration where it becomes mandatory for the treating physician to establish correct diagnosis and perform urgent surgery if the diagnosis is of operative cause. The correct interpretation of abdominal pain is one of the most challenging demand to any surgeon.1 It is of utmost importance to integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…15 Sabhnani G et al reported that majority of them with acute appendicitis were in the age group between 21 -40 yrs., which is in parallel to the current study findings where majority were in 21 -30 years' age group. 16 Kumar SK et al has also included the participants ranging between 7 -65 yrs. and males dominated the study which is similar to the current study findings.…”
Section: Discussionmentioning
confidence: 99%
“…15 Sabhnani G et al reported that majority of them with acute appendicitis were in the age group between 21 -40 yrs., which is in parallel to the current study findings where majority were in 21 -30 years' age group. 16 Kumar SK et al has also included the participants ranging between 7 -65 yrs. and males dominated the study which is similar to the current study findings.…”
Section: Discussionmentioning
confidence: 99%